Retrofit interventions in non-conditioned rooms: calibration of an assessment method on a farm winery. Issue 1 (2nd January 2017) - Barbaresi, Alberto; Dallacasa, Francesca; Torreggiani, Daniele; Tassinari, Patrizia
Abstract : In the Mediterranean area, most wine farms make use of unconditioned above-ground buildings for wine conservation and ageing. Those buildings are usually constructed without a specific temperature control design, therefore indoor temperature distributions and trends can be suboptimal for wine storage. At the same time, various elements (commonly available in farms such as straw bales and climbing plants) could be used to create cheap constructive solutions capable of improving building's thermal behaviour. This study aims to test the effectiveness of different retrofit interventions for thermal behaviour improvement in unconditioned above-ground farm buildings, referring to wine-ageing requirements. The alternative design solutions are evaluated through energy simulations, calibrated and validated on an Italian case study. The results show the importance of roof insulation, and the improved performance of the combination of more retrofit strategies. The proposed approach can be extended to other passive strategies and proves useful to provide information to optimize, or even avoid, conditioning systems.